Dehydration: Cause of fatigue or sign of pacing in elite soccer? - Edwards, A. M.; Noakes, T. D. (Sports Medicine, 2009)
Numerous studies have suggested that dehydration is a causal factor to fatigue across a range of sports such as soccer; however, empirical evidence is equivocal on this point. It is also possible that exercise-induced moderate dehydration is purely an outcome of significant metabolic activity during a game. The diverse yet sustained physical activities in soccer undoubtedly threaten homeostasis, but research suggests that under most environmental conditions, match-play fluid loss is minimal (~1-2% loss of body mass), metabolite accumulation remains fairly constant, and core temperatures do not reach levels considered sufficiently critical to require the immediate cessation of exercise. A complex (central) metabolic control system which ensures that no one (peripheral) physiological system is maximally utilized may explain the diversity of research findings concerning the impact of individual factors such as dehydration on elite soccer performance. In consideration of the existing literature, we propose a new interpretative pacing model to explain the self-regulation of elite soccer performance and, in which, players behaviourally modulate efforts according to a subconscious strategy. This strategy is based on both pre-match (intrinsic and extrinsic factors) and dynamic considerations during the game (such as skin temperature, thirst, accumulation of metabolites in the muscles, plasma osmolality and substrate availability), which enables players to avoid total failure of any single peripheral physiological system either prematurely or at the conclusion of a match. In summary, we suggest that dehydration is only an outcome of complex physiological control (operating a pacing plan) and no single metabolic factor is causal of fatigue in elite soccer.